In reply to the letter to the editor "Tele(oral)medicine: A new approach during the COVID-19 crisis" - Gilligan, Gerardo Marcelo; Piemonte, Eduardo David; Lazos, Jerónimo Pablo; Panico, René Luis (2021)
Fil: Gilligan, Gerardo Marcelo. Universidad Nacional de Córdoba. Facultad de Odontología. Departamento de Medicina Oral; Argentina.